Influence of parental occupation and school status on elementary students' internet competencies - Kuncahyono, Kuncahyono; Zubaidah, Siti; Susilo, Herawati; Kuncoro, Tri; Bilad, Muhammad Roil (Intelektual Pustaka Media Utama, 2025)
Understanding the factors influencing elementary school students' internet skills is critical in the rapidly evolving digital age. The research was conducted on the influence of gender, parental occupation, and school status on internet self-efficacy, interdependence, internet attitudes, and internet skills. Using logistic regression analysis, it was found that the male gender significantly affected internet self-efficacy and interdependence items with a value of p0.05; the largest finding on internet self-efficacy items showed a 3.846 times greater chance of helping others via the internet compared to females. Parents who work as non-government employees have a significant effect p05 on internet self-efficacy, interdependence, internet attitude, and internet skills items. The largest finding on internet skills is mainly increasing the ability to install applications in children, with 5.653 times greater odds than children from entrepreneurs. Students from private schools have the greatest chance of 3.840 times greater in developing internet skills information skills compared to public school students; significance (p0.05) was found in internet self-efficacy, interdependence, and internet skills items. The findings offer important insights for developing educational policies to improve primary school students' digital literacy, considering gender, parental occupation, and school status.